Speech acts and speech genres: the case of the compliment - Igor A. Sharonov (Слово.ру: балтийский акцент, 2024)
This article is devoted to the speech act of compliment, which is treated herein as expressing the speaker's attention and partiality to their interlocutor. The similarities and differences between speech acts of compliment and praise are analysed, with the characteristics of compliment linked to the gender and age of the interlocutor. Particular attention is paid to the concepts of speech act and speech genre and the applicability of these notions in analysing the speech act of compliment. When considering a compliment as an independent act, the concepts of 'speech act' and 'speech genre' serve as synonyms. When a compliment is part of a complex utterance consisting of several different speech acts, 'speech act' and 'speech genre' refer to disparate concepts. This article examines cases of compliment usage as an independent act (speech genre) and within other speech genres, such as requests, gratitude expressions, consolations and condemnations, where a compliment amplifies or mitigates the speaker's intention.